The characteristics of pressure injury photographs from the electronic health record in clinical settings. Issue 3 (13th December 2017) - Li, Dan; Mathews, Carol; Zhang, Fei
Abstract : Aims and objectives: To analyse and understand the characteristics of pressure injury images stored in the electronic health record. Background: To improve the quality of pressure injury documentation, photographing pressure injuries and storing the images in the electronic health record are standard practices in many hospitals. As new technologies develop, the utilisation of computer‐assisted image processing makes automatic measurement of pressure injury size and tissue segmentation through pressure injury images possible. The translation of new technological developments to pressure injury photography conducted in clinical environments faces obstacles such as the complexity of conditions in which photographs are taken. Design: A cross‐sectional descriptive study. Methods: A set of 360 pressure injury images were obtained from a hospital in western Pennsylvania. These images were taken in clinical settings during daily wound care service. The authors reviewed the pressure injury images to analyse the relative position of the pressure injury in the images, the shooting angle of the digital camera and the clinical objects in the background. Results: Only 5.9% of the pressure injury images were confined to only the wound region. In 80.1% of the images, the pressure injury is located in the central part of the image. In 54.0% of the images, the lens of the digital camera was not pointed perpendicularly to the plane of the pressure injury. Conclusions: Bedside wound assessment of pressure injuries and assessment from photographs of pressure injuries display reasonable agreement with pressure injury staging. To extract wound information (e.g., size and tissue type) from pressure injury images through novel image processing technologies, the characteristics of pressure injury images in clinical settings should be better understood during the development of tools for pressure injury image processing. Relevance to clinical practice: Our results can help image processing experts understand wound photography characteristics to shorten the gap between laboratory and clinical environments when translating new image processing technologies.